Elements Influencing Coopetitive Modes in a Cross-Border Value Chain - Nilova, Maria (My University, 2012)
Looking for expansion of value chain activities abroad competitor’s offer to cooperate in particular activities can strengthen or damage the company business. The managers have to choose in which activities it is more beneficial to cooperate and where to compete with a competitor. The modern managerial science calls the phenomenon coopetition and choice between cooperation and coopetition in activities is called a mode. Both have been proved in many previous studies; however, it is still questionable how to handle coopetition in a better way for the company. Thus, the current study contributes to the topic from three points: explanation of the decision about coopetition through the elements, coopetitive modes distribution in value chain activities and coopetition in international activities. In other words, the study aims to identify elements that stay behind a decision of coopetition and its modes in upstream and downstream activities in cross-border value chain. Preliminary assumptions about the elements were gathered through the existing theories applied for coopetition, viz. the business network approach, game theory and the transaction cost approach. The cases of Russian companies are in focus of the empirical study. Then the case studies done in qualitative manner through interviews and were conducted to investigate the elements from real business situations. Later the elements were grouped according to coopetitive modes and theoretical approaches. Then the findings were compared with the preliminary assumptions from the theory. The findings uncovered diversified nature of elements. Some elements could be explained by more than one theoretical approach. Other elements affected more than one coopetitive mode. However, due to fusion of theoretical approaches most of the elements found in the case studies were identified and explained presenting comprehensive and versatile picture of coopetitive relationships in value chain activities. The paper sheds light on why coopetition emerges in cross-border value and how and why coopetitive modes are distributed between upstream and downstream activities. For managers it has the main application helping to understand not only own reasons for coopetition but intentions of competitor before embedment in the relationships.
Keywords: Coopetition; Elements of Coopetition; Cross-Border Value Chain; Upstream Activities; Downstream Activities; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|